2014
DOI: 10.1242/jcs.149427
|View full text |Cite
|
Sign up to set email alerts
|

Functional interplay between MyoD and CTCF in regulating long-range chromatin interactions during differentiation

Abstract: BSTRACTHigher-order chromatin structures appear to be dynamically arranged during development and differentiation. However, the molecular mechanism underlying their maintenance or disruption and their functional relevance to gene regulation are poorly understood. We recently described a dynamic long-range chromatin interaction between the gene promoter of the cdk inhibitor p57 kip2 (also known as Cdkn1c) and the imprinting control region KvDMR1 in muscle cells. Here, we show that CTCF, the best characterized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…Crosslinked chromatin was subject to digestion and ligation, after which hybrid fragments, deriving from the ligation of Cdkn1c promoter and KvDMR1 sequences, were amplified as previously described. 23,24 The results reported in Fig. 2C show that 5-AZA treatment, in concomitance with decreased DNA methylation and increased MyoD binding, also caused a reduction of the interaction frequency between Cdkn1c promoter and KvDMR1, denoting the release of the chromatin loop.…”
Section: -Aza Treatment Restores the Functional Interaction Of Myod mentioning
confidence: 87%
See 4 more Smart Citations
“…Crosslinked chromatin was subject to digestion and ligation, after which hybrid fragments, deriving from the ligation of Cdkn1c promoter and KvDMR1 sequences, were amplified as previously described. 23,24 The results reported in Fig. 2C show that 5-AZA treatment, in concomitance with decreased DNA methylation and increased MyoD binding, also caused a reduction of the interaction frequency between Cdkn1c promoter and KvDMR1, denoting the release of the chromatin loop.…”
Section: -Aza Treatment Restores the Functional Interaction Of Myod mentioning
confidence: 87%
“…19 MyoD is the prototypical master regulator of differentiation 20 and induces Cdkn1c expression through a complex mechanism involving, on one hand, the mediation of MyoD-induced factors, which interact with Cdkn1c promoter 21,22 and, on the other hand, the direct interaction of MyoD with KvDMR1. 23,24 In particular, we found that, in undifferentiated myoblasts, KvDMR1 is involved in a repressive long-range chromatin interaction with Cdkn1c promoter, mediated by CTCF. Upon differentiation stimuli, MyoD binds to an E-box-like sequence adjacent to a CTCF binding site within KvDMR1, causing the disruption of the chromatin loop and the induction of maternal Cdkn1c expression.…”
mentioning
confidence: 80%
See 3 more Smart Citations